EDUCACIÓN SUPERIOR EN LA ADMINISTRACIÓN Y SU APRECIO LABORAL EN MÉXICO - Salazar-Fierro, Petra; Cortez, Rosa Corona; Hernández, Olegario Villa; Cuevas-Contreras, Tomás (European Scientific Journal, ESJ, 2015)
This essay addresses the issue of management higher education appreciation on labor context in Mexico. Some aspects and factors involved in the current phenomenon which seems that do not match the objectives of High Education Institutions (HEI) to the needs of the business sector of the country are exposed. Education competency, implementation and certification of quality systems as important factors in order to develop students holistically in those skills than the workforce demand arise. The conclusion that there are inconsistencies in the premises stated, due the fact of having a career is not synonymous of getting a good job and proper wage. It is required coordination and cooperation among agencies, institutions and companies to improve this situation, creating fast and efficient strategies to achieve an effective implementation.